Game-based learning in teaching grammar for non-native speakers: a systematic review - Janaki Manokaran,; Norizan Abdul Razak,; Afendi Hamat, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2023)
The emergence of Industrial Revolution 4.0 targets challenging the norm and pushing boundaries. Hence, educational institutions are expected to embrace a few methods to adopt technology as part of their instructional strategies. The incorporation of technology can nurture students' motivation to learn English, particularly grammar. While game based grammar learning provides motivation, enjoyment, and acquisition of grammar knowledge, trends in using game-based grammar learning have not been scrutinised in the context of a systematic review. Therefore, this paper reviewed articles on game-based grammar learning beginning in 2016 through 2021. The review summarises articles in the following categories: 1) research contextual dimension, 2) methodological dimension, 3) game dimension, and 4) outcomes dimension. By reviewing 25 articles, this systematic review could serve as a guide for designing language teaching and learning activities using a game-based approach. Based on the findings, the paper presents implications and suggestions for future research in terms of optimised delivery of knowledge using game-based grammar learning.